Wabi - Sabi and the Nature of Knowledge - Rudolf Cymorr Kirby Martinez (San Beda University, 2019)
This paper explores the parallel nature of Wabi-sabi, the Japanese aesthetic principle of beauty and our understanding of the nature of knowledge: that they are impermanent, imperfect, and incomplete. It further gives emphasis on the implied ethical and moral obligation of the social scientist in the continued dissemination of knowledge given its inherent nature.